Legal Protection of Land Rights in Mixed Marriages Ending in Divorce: Perlindungan Hukum Hak Atas Tanah dalam Perkawinan Campuran yang Berakhir dengan Perceraian - Damanik, Pandapotan; Damanik, Shem Yafet Cundus Pratama (Indonesian Journal of Law and Economics Review, 2024)
General Background: Mixed marriages in Indonesia face legal complexities, especially regarding property division upon divorce due to differing national laws. Specific Background: Conflicts between the Basic Agrarian Law (UUPA) and the Civil Code (KUHPerdata) complicate land ownership rights in these marriages. Knowledge Gap: Few studies address the protection of Indonesian citizens’ land ownership rights in mixed marriages ending in divorce. Aims: This study analyzes the legal protection of these rights and identifies existing obstacles. Results: Key challenges include legal jurisdiction complexities and a lack of prenuptial agreements, leading to legal uncertainties. Novelty: This research focuses on the interplay between national land ownership laws and international marital dissolution. Implications: The study suggests the necessity for stronger prenuptial agreements and reforms to better protect land ownership rights post-divorce, enhancing legal certainty and fairness. Highlights: Legal Conflicts: Highlights how discrepancies between the UUPA and KUHPerdata complicate land ownership rights. Prenuptial Agreements: Emphasizes the critical need for robust prenuptial agreements in mixed marriages. Legal Reform: Calls for reforms to improve legal protections for land ownership rights post-divorce. Keywords: Mixed Marriage, Land Ownership, Divorce, Legal Protection